Association of Nephropathy with the Thyroid Profile - Tahir, Ali; Tuz-Zahra, Fatima-; Tipu, Imran (BioScientific Review, 2020)
The thyroid gland produces two hormones: thyroxin (T4) and triiodothyronine (T3). The thyroid hormone affects both the kidney morphology and its functions. Kidneys are involved in the metabolism and elimination of the thyroid hormones. The current study was conducted on 100 nephropathy patients, of which 57 were female patients and 43 were male patients. Venous blood samples were collected for the estimation of hyperthyroidism in nephropathy patients. Thyroid stimulating hormone (TSH), thyroxin, and triiodothyronine were estimated using the chemilumeniscent techniques. Serum creatinine levels were estimated through the modified kinetic phenomenon (Jaffe’s reaction). Serum urea levels were estimated through the urease method and uric acid levels were recorded. The mean age of hypothyroid patients was 37.38 years. It was 34.13 years for patients with the hyperthyroid state, while for the normal patients it was 35.46 years. Women comprised 70% of the hypothyroid patients, whereas among the normal patients their percentage was 29%. Serum TSH level (7.11 ± 0.001 mIU/L) was significantly higher in hypothyroid patients, although it decreased in hyperthyroid patients (0.22 ± 0.001) as compared to the corresponding values in healthy patients (2.54 ± 0.001). The values of T3 (52.3 ± 0.05 ng/dl) and T4 (2.217 ± 0.001) decreased slightly in hypothyroid patients as compared to the healthy patients (104 ± 0.001 and 6.667 ±0.001 respectively), although they remained statistically significant. T3 (356.12 ± 0.001) and T4 (17.99 ± 0.001) significantly increased in hyperthyroid patients. The correlation between thyroid dysfunction and nephropathy was found to be significant. Gender and age proved to be the most important factors for these pathological conditions. Renal function biomarkers including GFR, serum creatinine, urea and uric acid were found to have an association with changes in the thyroid hormones. Copyright(c) The Authors